Humanitarian Intervention and the Rwandan Genocide: Nothing More Than a "Band-Aid Solution" / L’intervention humanitaire et le génocide rwandais: Rien de plus qu’une «solution pansement» - Farrell, Matthew P. (Glendon Journal of International Studies, 2013)
Abstract: Is humanitarian intervention really a solution to humanitarian crises? This article will attempt to provide evidence that without serious re-evaluation of the mechanisms whereby military and socioeconomic humanitarian intervention is carried out internationally, humanitarian intervention cannot be more than a "Band-Aid solution"to improving the situation of intended beneficiaries. To prove this point, the short- and long-term benefits and disadvantages of humanitarian intervention during and in the wake of the Rwandan genocide will be examined and evaluated. Particular attention will be paid to the repercussions of socioeconomic humanitarian intervention. It is concluded that humanitarian aid in Rwanda was of greater economic than humanitarian benefit. Subsequently, policy recommendations will be made to improve the benefit of future humanitarian interventions by creating a United Nations standing army, increasing international commitment to providing disinterested aid, and by creating a pool of financial resources exclusively dedicated to preserving human rights and addressing humanitarian crises. Résumé: Est-ce que l’intervention humanitaire est vraiment une solution aux crises humanitaires? Cet article tentera de démontrer que, sans réévaluation sérieuse des mécanismes par lesquels l’intervention humanitaire militaire et socio-économique est effectuée au niveau international, l’intervention humanitaire ne peut pas être plus qu’une «solution pansement» dans l’amélioration des conditions de vie des populations ciblées. Nous soutiendrons cette thèse en évaluant plus particulièrement les avantages à court et à long terme ainsi que les inconvénients de l’intervention humanitaire pendant et à la suite du génocide rwandais. Une attention particulière sera accordée aux répercussions socio-économiques de cette intervention humanitaire afin de démontrer qu’elle était plus économique qu’humanitaire. Nous ferons également des recommandations dans le but d’améliorer l’impact des interventions humanitaires à venir, notamment en suggérant la création d’une armée permanente des Nations Unies, d’accroître l’aide internationale désintéressée, et de créer un schème de financement exclusivement dédié à la préservation des droits de la personne et aux crises humanitaires.